Two new species of Fittkauimyia Karunakaran (Diptera: Chironomidae) from Brazil - Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2013)
Two new species of the genus Fittkauimyia from Brazil are described and illustrated. Fittkauimyia mayumiae sp. n. from Amazonian forest is described based on adult male, female and pupae and F. carranquensis sp. n. from mountainous re-gion of southeast is described based on adult male and pupae.